Anthropometric and body composition of Universiti Teknologi MARA Pahang football players (Pahang Tigers) during competitive season / Muhd Sufyan Mohd Zaki … [et al.] - Mohd Zaki, Muhd Sufyan; Linoby, Adam Feizrel; Basar, Annisaa; Mohd Afandi, Mohd Azizul; Mohd Azam, Mohd Zulkhairi (2012)
Football is the most enjoyable sport in the world and will be played continuously at different level of match. Universti Teknologi MARA (UiTM) Pahang football team may be considered as a serious contender in competitive football tournament recently. The series of victory in every match in Liga IPT 2012 Division 3 allow the team to be promoted in Division 2 for next season. This study was undertaken to record the anthropometric and body composition of the players who were responsible of this great achievement. A total of 15 football players were involved that consist of three main roles in the team (midfielder, defender and striker). The data were included the height, weight and body fat percentage of the players. Subjects mean age was 19.6 (± .63) years. The mean body weight and height (± SD) were 59.3 (± 5.92) kg and 170.8 (± 3.98) cm respectively. All testing were in accordance to standardized procedures. Overall findings based on one-way ANOVA did not reveal significant differences in terms body fat percentage based on the three specific playing positions. Major cause for the current findings was due to the limited number of participants in this study. This collective data will set as a physically status that permit the modification of dietary intakes and training programs to sustain fitness and match performance throughout the football competitive season. Thus, preliminary descriptive analysis proposes that anthropometric and body composition of the players in this team significantly contributes to their successful performance in the tournament